Chaotic communication. - Mullins, J. (IEEE spectrum)
This paper reports how European researchers were able to use the chaos phenomenon to send digital messages at gigabit per second speeds over 115 km of commercial optical fiber beneath the streets of Athens, Greece. A distinct advantage of chaotic communication is that it is often easier to generate robust, high-power chaotic signals than conventional ones. A chaotic signal is also harder for an eavesdropper to identify because it is difficult to distinguish from background noise.